Diet and first documented data on plastic ingestion of Trachinotus ovatus L. 1758 (Pisces: Carangidae) from the Strait of Messina (central Mediterranean Sea). Issue 1 (2nd January 2016) - Battaglia, P.; Pedà, C.; Musolino, S.; Esposito, V.; Andaloro, F.; Romeo, T.
Abstract: The present paper investigates the diet and the food composition of Trachinotus ovatus in the central Mediterranean Sea (Strait of Messina). Moreover, the first documented data on plastic ingestion by T. ovatus are also reported. Samples ranging between 16.5 and 28.0 cm fork length were collected between May and November 2012 in the Strait of Messina (central Mediterranean Sea) by trolling lines. T. ovatus fed mainly on pelagic crustaceans and fishes, although the contribution of mollusks was also important. The absence of dominant prey indicated a generalist feeding behavior. The plastic debris was found in the stomach content of T. ovatus with a high percentage of occurrence (%O = 24.3%). Considering the commercial interest that T. ovatus has in some small-scale fishery markets, the potential impact of plastics on the trophic web and human consumption should be investigated.